2001
DOI: 10.4319/lo.2001.46.5.1214
|View full text |Cite
|
Sign up to set email alerts
|

A test of the ashߚfree dry weight technique on the developmental stages of Patiriellaspp. (Echinodermata: Asteroidea)

Abstract: Determination of the ashߚfree dry weight (AFDW) of marine specimens requires samples to be rinsed, soaked, and centrifuged. Problems associated with this technique were examined with the developmental stages of seastar species (Patiriella) with different modes of development. The influence of three rinsing solutions (ammonium formate [AF], filtered seawater [FSW], and reverse osmosis water [RO]) was assessed. The hypothesis that the AFDW technique is a measure of organic material was addressed by drying inorga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Estimating AFDW is simple, but this method contains a number of potential sources of error. Sample preparation is one; salts are hygroscopic and, if not removed from the exterior of marine organisms prior to drying, can cause samples to gain weight after ashing (Moreno et al, 2001), leading to an underestimate of AFDW. This phenomenon can be minimized by rinsing marine samples with ammonium formate (isotonic with seawater) or in some cases with distilled water to remove surface salts.…”
Section: Or What Are the Biochemical Constituents Of An Egg And Howmentioning
confidence: 99%
See 1 more Smart Citation
“…Estimating AFDW is simple, but this method contains a number of potential sources of error. Sample preparation is one; salts are hygroscopic and, if not removed from the exterior of marine organisms prior to drying, can cause samples to gain weight after ashing (Moreno et al, 2001), leading to an underestimate of AFDW. This phenomenon can be minimized by rinsing marine samples with ammonium formate (isotonic with seawater) or in some cases with distilled water to remove surface salts.…”
Section: Or What Are the Biochemical Constituents Of An Egg And Howmentioning
confidence: 99%
“…This phenomenon can be minimized by rinsing marine samples with ammonium formate (isotonic with seawater) or in some cases with distilled water to remove surface salts. Disturbingly, though, Moreno et al (2001) found that some inorganic salts retain water at normal drying temperature (80°C) but lose it at ashing temperatures (450°C); thus, even in well-rinsed samples, water may be retained by intracellular salts in "dried" samples only to be burned away at 450°C, leading to an overestimate of AFDW. Finally, AFDW measurements do not capture the differing energetic values of lipids, carbohydrates, and proteins (Podolsky, 2002), so AFDW may not be suitable for comparing samples in which biochemical composition is likely to differ.…”
Section: Or What Are the Biochemical Constituents Of An Egg And Howmentioning
confidence: 99%